The Admissibility of an Audio Recording in Lithuanian Civil Procedure and Arbitration - Bartkus, Jurgis (Teisė, 2021)
This article analyzes the issues related to the admissibility of audio recordings in Lithuanian civil proceedings and arbitration. The study critically evaluates the statutory law, case law and legal doctrine related to the admissibility of audio recordings. The study reveals that the case law of the Supreme Court of the Republic of Lithuania on the admissibility of audio recordings has to be improved on the application of the criteria of admissibility of audio recordings and on the protection of privacy. Meanwhile in Lithuanian arbitration law, it is suggested to waive the arbitration court’s discretion to decide on the possible approaches to the admissibility of an illegally made audio recording and to follow the view that an illegally made audio recording is per se inadmissible.